Dimensionite: the new revolution of modern textbook - Ibrahim, Aisyah Hafizah; Abd Ghani, Farhanna; Thian, Bernard Yi Zhe; Saad, Wan Zuhainis (Centre for Global Open Access Learning, Immersive Technology & Quality Assurance, Universiti Sains Islam Malaysia, 2017)
Dimensionite is an app which implements both Augmented and Podcast into a game learning app which prepares for today Future Ready Learners into the world of Food Microbiology that can be played individually or teamwork. Updating today news to Dimensionite, users now able to discover the impacts of food microbiology which can be learned when playing the app in Dimensionite.